Identification of freshwater prawns from the dam and streams around the University of Riau, Pekanbaru - Hermawita, Ade; Putra, Ridwan Manda; ', Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Dam and streams around the University of Riau is inhabited by many types of aquatic organism, including prawns. Scientific information of those organisms, however, is almost none. To understand the types of freshwater prawns present in that area. A research has been conducted from February to April 2017. Sampling areas were in the dam, pond and streams around the University of Riau. Freshwater prawns sampling were conducted once/week for a month period. Prawns were caught using a scoop net (mesh sixe 0,5 cm). Morphometrical and meristical characteristics of the prawns were then analyzed descriptively. The prawns sampled were identified. There were 106 prawns. The freshwater prawns species present were consisted of a single species only, namely Macrobrachium tolmerum, Riek, 1951 (Palaemonidae). This species characterized by schapocherite length that is shorter than rostrum length, rostral teeth sub-equally spaced, 8-10 teeth in the dorsal and 4 teeth in the ventral of rostrum. In male, the rostrum, propodus, carpus and merus are longer than those of the female.